Improving The Quality of Process Standard Based on School-Based Management - Anang Taufik Karunia; Maswardi M. Amin; M. Chiar (STKIP Singkawang, 2018)
The purpose of this research is to understand and describe in detail and depth about 1) Planning of standard quality improvement process based on school-based management at State Junior High School 3 Singkawang (SMPN 3 Singkawang); 2) Organizing the improvement of process standard quality based on school-based management in SMP N 3 Singkawang; 3) Implementation of standard quality improvement process based on school-based management in SMP N 3 Singkawang; 4) Supervision of standard quality improvement process based on school-based management at SMP N 3 Singkawang; 5) obstacles and efforts in improving the quality of process standards based on School-basedmanagement in SMPN 3 Singkawang. The approach used in this research is qualitative research using case study method. then the results obtained in this study as follows 1) Planning standard quality improvement process based on theschool-based management SMPN 3 Singkawang in good categorize; 2) Organizing the improvement of process standard quality based on school-based management of SMPN 3 Singkawang is categorized well; 3) Implementation of standard quality improvement process based on school-based management of SMPN 3 Singkawang is categorized quite well; 4) Supervision of standard quality improvement process based on school-based management of SMPN 3 Singkawang is categorized quite well; 5) Obstacles in improving the quality of process standards based on the school-based management of SMPN 3 Singkawang is the condition of facilities still not meet the standards, especially the land or building, the physical condition of teachers caused by the age factor but the quality improvement of educators developed through certification of educators and other activities that support the learning process as well as the establishment of harmonious relationships between schools, parents and alumni.